Advances in early detection of non‐small cell lung cancer: A comprehensive review - Nour Kenaan; George Hanna; Moustafa Sardini; Mhd Omar Iyoun; Khedr Layka; Zein Alabdin Hannouneh; Zuheir Alshehabi (Cancer Medicine)
Abstract Background Lung cancer has the highest mortality rate among malignancies globally. In addition, due to the growing number of smokers there is considerable concern over its growth. Early detection is an essential step towards reducing complications in this regard and helps to ensure the most effective treatment, reduce health care costs, and increase survival rates. Aims To define the most efficient and cost‐effective method of early detection in clinical practice. Materials and Methods We collected the Information used to write this review by searching papers through PUBMED that were published from 2021 to 2024, mainly systematic reviews, meta‐analyses and clinical‐trials. We also included other older but notable papers that we found essential and valuable for understanding. Results EB‐OCT has a varied sensitivity and specificity—an average of 94.3% and 89.9 for each. On the other hand, detecting biomarkers via liquid biopsy carries an average sensitivity of 91.4% for RNA molecules detection, and 97% for combined methylated DNA panels. Moreover, CTCs detection did not prove to have a significant role as a screening method due to the rarity of CTCs in the bloodstream thus the need for more blood samples and for enrichment techniques. Discussion Although low‐dose CT scan (LDCT) is the current golden standard screening procedure, it is accompanied by a highly false positive rate. In comparison to other radiological screening methods, Endobronchial optical coherence tomography (EB‐OCT) has shown a noticeable advantage with a significant degree of accuracy in distinguishing between subtypes of non‐small cell lung cancer. Moreover, numerous biomarkers, including RNA molecules, circulating tumor cells, CTCs, and methylated DNA, have been studied in the literature. Many of these biomarkers have a specific high sensitivity and specificity, making them potential candidates for future early detection approaches. Conclusion LDCT is still the golden standard and the only recommended screening procedure for its high sensitivity and specificity and proven cost‐effectiveness. Nevertheless, the notable false positive results acquired during the LDCT examination caused a presumed concern, which drives researchers to investigate better screening procedures and approaches, particularly with the rise of the AI era or by combining two methods in a well‐studied screening program like LDCT and liquid biopsy. we suggest conducting more clinical studies on larger populations with a clear demographical target and adopting approaches for combining one of these new methods with LDCT to decrease false‐positive cases in early detection.